Countering Common Arguments Against Taxes on Sugary Drinks - Hattersley, Libby; Thiebaud, Alessia; Silver, Lynn; Mandeville, Kate (World Bank, Washington, DC, 2020)
Implementing governments need to be prepared to face considerable opposition in introducing and defending a new sugar-sweetened beverage (SSB) tax. Arguments against SSB taxes tend to closely mirror those used against tobacco taxes, including that these taxes are not effective, are regressive (place a disproportionate burden on lower income groups), negatively affect employment and economic growth, and violate international, regional, or national law. Around the world, these arguments have been used very effectively by opponents to impede and undermine public and political support for SSB taxes, both proposed and existing. Yet, as this evidence brief shows, these arguments are not supported by sound evidence. Common arguments against SSB taxes are outlined below, along with the evidence that can be used to counter each proposition.